Characterization of the salinity in soils of the San Pedro River floodplain, Nayarit, Mexico - Ortega-Escobar, Héctor Manuel; Martínez-Rodríguez, Oscar Germán; Can-Chulim, Álvaro; Cruz-Crespo, Elia; Bojórquez-Serrano, José Irán; García-Paredes, Juan Diego; Sánchez-Bernal, Edgar Iván; Madueño-Molina, Alberto; Mancilla-Villa, Oscar Raúl (REVISTA TERRA LATINOAMERICANA, 2023)
The floodplain of the San Pedro River, a fluvial-delta formation, is one of the coastal areas affected by marine intrusion during the last glaciation. In this region, agriculture is the main economic activity; however, intensive agricultural practices, the geological past, current interactions with the marine system and the transport of salts through sediments and water make this area susceptible to soil salinization. To characterize the salinity of the agricultural area of the San Pedro River floodplain, two soil samplings were carried out at 91 sites over a period of two years. Samples were taken from depths of 0.0 to 0.3 m and from 0.0 to 0.1 m to depths of 1 m and 3 m. Fifty groundwater samples were collected. Saturation extracts were obtained (1: θsat) from the soil samples. For the soil and groundwater extracts, the pH, EC, and major cations and anions were determined, the sodium adsorption ratio was calculated in the original and adjusted formulations (SARor and SARadj), and the exchangeable sodium percentage (ESP) was ascertained. The pH, EC and SARor of the groundwater ranged from 6.94 to 8.37, 199 to 4660 µS cm-1 and 0.16 to 32.30 (mmolc L-1)1/2, while in the saturation extracts, the pH, EC and SARor ranged from 4.81 to 8.58, 0.08 to 72.4 dS m-1 and 0.11 to 33.09 (mmolc L-1)1/2, respectively. The salinity problems in the study area are closely related to the intrusion of salts from the marine system.